Effectiveness of yoga training program on the severity of autism. (August 2017) - Sotoodeh, Mohammad Saber; Arabameri, Elahe; Panahibakhsh, Maryam; Kheiroddin, Fatemeh; Mirdoozandeh, Hatef; Ghanizadeh, Ahmad
Abstract: This study examines the effect of yoga training program (YTP) on the severity of autism in children with High Function Autism (HFA). Twenty-nine children aged 7 to 15 (mean = 11.22, SD = 2.91) years were randomly allocated to either yoga or control group. The participants in the yoga group received an 8-week (24-session) Yoga Training Program (YTP). Parents or caregivers of participants completed autism treatment evaluation checklist (ATEC) at baseline and the end of the intervention. The results of the analysis showed that there were significant differences between the two groups with regards to all ATEC sub-scores except ATEC I (speech/language/communication). This study provides support for the implementation of a yoga training program and identifies specific procedural enhancements to reduce the severity of symptoms in children with autism. Highlights: Yoga poses decreased the severity of disease in children with autism. Yoga poses do not have any significant effect on speech and language sub-scores of ATEC. Yoga poses have a significant effect on sociability sub-scores of ATEC. Yoga poses have a significant effect on cognitive and awareness sub-scores of ATEC. Yoga poses have a significant effect on health and physical behavior sub-scores of ATEC.